PEMBUATAN CAIRAN PEMBERSIH ALAMI DARI KULIT JERUK - Yoshida, Debbie (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
One of the problems in environmental management is waste. Waste has a bad impact on humans and the environment. However, rubbish/waste can have benefits by being sorted and reprocessed. Most of the waste comes from households. The service team provides education about the use of orange peel waste which can be used as a natural cleaning fluid. Community service activities are one of the Tri Dharma of Higher Education in addition to carrying out education and research. With the community service program, it is hoped that mothers and the community of Tomang Village, West Jakarta will gain knowledge about processing household waste/garbage. Implementation method with counseling and demonstration/practice. The results achieved are very good. With the demonstration, participants can practice directly making natural cleaning fluids that can be used to clean stoves, clean sinks, freshen toilets and so on. The knowledge and skills presented provide provisions for mothers and the community in processing waste at a basic level (self-processing) which can later be used by themselves and become economically valuable and can also become a business opportunity to improve family welfare.